Analysis on the optimization measures of the management mode of digital transformation company from the perspective of internal control - Wu, Jinlong (Transactions on Economics, Business and Management Research, 2024)
This paper conducts an analysis on the optimization measures for the management mode of digital transformation companies, specifically from the perspective of internal control. It delves into the challenges and opportunities faced by companies undergoing digital transformation and explores how internal control mechanisms can be leveraged to enhance the effectiveness and efficiency of these transformations. The study examines various aspects of internal control, including risk assessment, information and communication, control activities, monitoring, and the control environment, and discusses how these elements can be optimized to support the digital transformation process. By adopting a comprehensive and systematic approach, the paper aims to provide practical insights and recommendations for companies seeking to optimize their management modes in the context of digital transformation.